1997
DOI: 10.2307/3345427
|View full text |Cite
|
Sign up to set email alerts
|

Elementary, Middle, and High School Student Perceptions of Tension in Music

Abstract: School-age students from Grades 2, 5, 8, and 11/12 (N = 112) were asked to listen to a recording of thefirst movement of Haydn's Symphony No. 104. Al subjects were asked to record theirperception of "tension " in the music using a Continuous Response Digital Interface (CRDI) dial. As in previous studies of this type (Fredrickson, 1995;Madsen & Fredrickson, 1993), no definition of the term in question was given, allowing subjects to, in essence, create their own definition. Graphic analysis showed that even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 22 publications
8
45
0
Order By: Relevance
“…This is corroborated by empirical research showing that subjective ratings of musical tension correlate with ratings of discrete emotions (sadness, fear, and happiness) and physiological responses during music listening (Krumhansl, 1997). It has furthermore been shown that subjective ratings of musical tension correlate highly within individuals between different exposures to the same music piece (Krumhansl, 1996) as well as between different groups of persons such as musicians and nonmusicians or school children of different ages (Fredrickson, 1997(Fredrickson, , 1999(Fredrickson, , 2000, suggesting relatively consistent and stable underlying cognitive and affective processes.…”
Section: A Striking Feature Of Music Is Its Abilitysupporting
confidence: 57%
“…This is corroborated by empirical research showing that subjective ratings of musical tension correlate with ratings of discrete emotions (sadness, fear, and happiness) and physiological responses during music listening (Krumhansl, 1997). It has furthermore been shown that subjective ratings of musical tension correlate highly within individuals between different exposures to the same music piece (Krumhansl, 1996) as well as between different groups of persons such as musicians and nonmusicians or school children of different ages (Fredrickson, 1997(Fredrickson, , 1999(Fredrickson, , 2000, suggesting relatively consistent and stable underlying cognitive and affective processes.…”
Section: A Striking Feature Of Music Is Its Abilitysupporting
confidence: 57%
“…The tension judgment is sensitive to changes in a performance [6], and it depends on a wide variety of structural, harmonic, and rhythmic features in the music [16] [14] [6] [10] [12]. This measure is consistent across age groups, musical skill levels, and levels of familiarity with the stimulus music [7] [8] [9] [10]. It is an informative and consistent measure.…”
Section: Introductionmentioning
confidence: 99%
“…Research utilizing the CRDI for perception of musical tension and individual variables has included effects of conductor (Fredrickson, 1994), performer use of rubato (Fredrickson & Johnson, 1996), age and/or sophistication of the listener (Fredrickson, 1997a), participation in rehearsal/performance (Fredrickson, 1999), listeners' musical proficiency (Fredrickson, 2000), dynamics (Misenhelter, 2001), performance medium (Fredrickson, 2001), jazz music (Fredrickson & Coggiola, 2003), music and text (Hackworth & Fredrickson, 2009), as well as artistic tension in dance (Frego, 1999).…”
mentioning
confidence: 99%